A Rare Case of Extrinsic Stenosis of Dural Sinus. Issue 1 (30th September 2022) - Boyer, Axel; Deprez, Louis
Teaching Point: Dural sinus stenosis are a rare cause of increased intracranial pressure and can be treated in some cases by stenting.